Are competitiveness rankings and institutional measures helping emerging economies to improve? (2023)
Purpose – Based on the rankings of the global competitiveness index and the fragile states index, this paper aims to suggest alternative approaches to shed some light on the effectiveness of rankings in helping emerging economies improve their competitiveness from an institutional standpoint. Design/methodology/approach – The statistical analysis consisted of a two-stage analysis; the first stage consisted of constructing an updated Alternative Institutional Quality Index (AIQI), intending to design a comparative measure between dimensions over time. The second stage consisted of evidencing the structure of each of the observed dimensions’ variance to evidence the existing changes or gaps of the AIQI and its components. The authors incorporated the Kruskas–Wallis (KW) model to test the results. Findings – This paper demonstrates that the analyzed countries generally maintain their competitive position, even though changes in their scores are reflected. This makes invisible the development and progress factors generated by the countries that are mainly found with low scores and only reflect stable structures that allow them to maintain their position. Research limitations/implications – The current study has a limitation because it concentrated on a few selected indicators based on the literature review. The limitations of this research may be overlooked in the future by adding additional variables and observations. The paper could be improved by including intraand inter-regional approaches to control based on the occurrence of specific circumstances (i.e. informal institutions, economic development or factor endowments). Practical implications – The paper contributes to the applicable measurement of competitiveness and its structural change over time. Originality/value – This paper proposed an alternative and simple methodology to assess the evolution of the competitiveness indicators; this methodology could be used to measure structural changes at different levels, which may be an input for the design and implementation of policies to foster competitiveness.